IBM Spectrum Protect Plus Practical Guidance for Deployment, Configuration, and Usage - Dufrasne, Bertrand; Becker, Gerd; Bode, Chris; Ramos, Alberto; Gaschler, Andre; Westphal, Axel; Lindström, Mikael; Minig, Peter; Sauvanet, Julien; Stuber, Martin; Stumpf, Markus; Uríča, Jozef; et al. (IBM Redbooks, 2021)
IBM® Spectrum Protect Plus is a data protection solution that provides near-instant recovery, replication, retention management, and reuse for virtual machines, databases, and applications backups in hybrid multicloud environments. IBM Knowledge Center for IBM Spectrum® Protect Plus provides extensive documentation for installation, deployment, and usage. In addition, build and size an IBM Spectrum Protect Plus solution. The goal of this IBM Redpaper® publication is to summarize and complement the available information by providing useful hints and tips that are based on the authors' practical experience in installing and supporting IBM Spectrum Protect Plus in customer environments. Over time, our aim is to compile a set of best practices that cover all aspects of the product, from planning and installation to tuning, maintenance, and troubleshooting.